Finite Elemental Analysis of Industrial Structure Using Cold Formed Steel - Patidar, Pradeep; Bedi, Komal (International Journal of Scientific Research in Civil Engineering, 2019)
Increasing world population and natural resource limitations has led to a growing demand for more efficient structural systems to achieve a sustainable economy and society. Cold-formed steel CFS) Structural systems are increasingly adopted as primary or secondary structural members in modern building construction because of their light weight, speed of construction, recyclability, and sustainability. However, the inherently low buckling resistance of thin sections results in relatively low strength and ductility in CFS elements, which limits their performance in tall buildings and under extreme loading events. The pre-engineered steel building system construction has great advantages to the single storey buildings, practical and efficient alternative to conventional buildings, the System representing one central model within multiple disciplines. Pre-engineered building creates and maintains in real time multidimensional, data rich views through a project support is currently being implemented by Staad pro software packages for design and engineering.In this research work we will design Industry using analysis tool Staad.pro and use Novel cold formed steel structure and compare it with general steel available in Indian market. Here we will compare both in terms of strength and weight of structure with bolted and welded connections.